2023
DOI: 10.1111/raq.12824
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of functional feed additives to produce cost‐effective, ecofriendly aquafeeds high in plant‐based ingredients

Abstract: Fishmeals (FM) are the most superior protein sources in aquafeed. World‐wide growing demand and limited supply of FM limit its use as sole protein sources in aquafeed and force fish nutritionists to develop alternate protein‐based aquafeeds. However, increasing alternate proteins over a certain percentage reduces fish performance. Many attempts have been made (viz., manipulation of processing technology of feed ingredients and feed formulations, supplementation strategy) to overcome the negative effects of inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 344 publications
(594 reference statements)
0
7
0
Order By: Relevance
“…According to Hossain et al (2023) , this effect on immune response may have been caused by the MOS's influence on the immune response, enhanced intestinal absorption of certain nutrients, including Zn, Cu, and Se, or a combination of the 2. Much of the nature of the mechanism responsible for MOS-related immunomodulation is yet unknown.…”
Section: Discussionmentioning
confidence: 99%
“…According to Hossain et al (2023) , this effect on immune response may have been caused by the MOS's influence on the immune response, enhanced intestinal absorption of certain nutrients, including Zn, Cu, and Se, or a combination of the 2. Much of the nature of the mechanism responsible for MOS-related immunomodulation is yet unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The supply of fish meal for aquafeed is continuing to decrease, and the aquatic environment is deteriorating with the rapid rise of aquaculture ( Han et al, 2018 ). Generally, aquatic feed accounts for 50%–60% of the total cost in aquaculture ( Hardy, 2010 ), and its quality is closely related to the production efficiency of aquaculture and the output of waste discharged into surroundings ( Hossain et al, 2023 ). Hence, successful sustainable aquaculture in the future heavily depends on the efficiency of the artificial feed.…”
Section: Introductionmentioning
confidence: 99%
“…However, high inclusion of these ingredients in aquafeeds is limited due to an imbalance in essential amino acids, the presence of antinutritional factors, inconsistent quality and low palatability and digestibility [ 2 , 9 , 17 , 18 ]. Recent studies have shown that some of the problems associated with alternative plant and animal ingredients can be partly addressed by the incorporation of functional feed additives in the diet [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Functional feed additives are defined as nutritive/non-nutritive compounds that are included in feed formulations to serve a specific function, such as improving the physical or chemical properties of the diet or the performance and quality of fish and their resulting products [ 18 , 19 , 20 ]. There are a variety of feed additives, quite diverse in their chemical nature, being used in feed formulations [ 19 ].…”
Section: Introductionmentioning
confidence: 99%